Perceived success factors and challenges towards franchise sustainability in South Africa: A franchisor perspective - Pillay, Shalendra Kumaran. (My University, 2014)
ABSTRACT South Africa as a country faces a number of challenges that stifle its economic growth, some of which include the high unemployment rate, the growing disparity between the rich and the poor in the country, as indicated by the Gini coefficient, which has increased from 0.66 in 1993 to 0.70 in 2008 (Leibbrandt, Woolard, Finn, & Argent, 2010) and the poor education and skills levels, to name a few. The South African government stated that it could only overcome these challenges if it worked closely with business, labour and community constituencies to pursue these objectives. Small and medium enterprises (SMEs) have been identified as vehicles for job creation in South Africa, however, 70-80 percent of SMEs in South Africa fail (Brink, Cant, & Ligthelm, 2003). South Africa needs to create more sustainable SMEs that can be used to combat the high unemployment rate that the country is challenged by. These SMEs can be further used to facilitate the transfer of skills and knowledge, thereby assisting in improving education and skills levels within the country. Electronic online survey questionnaires were presented to senior managers and directors within franchisor head offices. The study statistically compared the success factors, challenges and enabling structures of franchising that allows the franchising business model to be a more sustainable form of SME. The results of this study reinforced many of the findings of previous researchers. This study found that the key attributes of successful franchisees as perceived by the franchisor were desire to succeed; motivation; management ability; financial backing; and being a self-starter. The key challenges of franchisees as perceived by the franchisor included lack of management skills of the franchisee; the lack of financial knowledge of the franchisee; access to finance and working capital; the lack of business experience of the franchisee; and the lack of sufficient skilled staff. The enabling support and add-on services as perceived by the franchisor that needed to be offered to assist the franchisee in overcoming the challenges were the provision of standard operating manuals; the provision of add-on services such as operations and performance, management training, compliance training, site allocation and financial training for the franchisee; the provision of operations managers to assist or monitor franchisees with daily operations; and the assurance of higher frequency of visits with franchisees by the operations managers. This study identified the factors that contributed to the sustainability of the franchisees’ business as growing revenue; profitably acquiring and retaining customers; increasing operating speed and adaptability; reducing costs and increasing efficiencies; and innovating to achieve competitive advantage.
MBA 2014
Keywords: Franchises (Retail trade)